Integration of Maqasid Shariah in the Implementation of Digital Zakat based on the E-Zakat Platform at BAZNAS Surabaya - Saoki, Saoki; Mahir, Mahir (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2025)
This study analyses the implementation of electronic zakat payments (E-Zakat) from the perspective of compliance with the three features of maq>asid shariah. The use of E-Zakat raises crucial issues related to accuracy and transparency. This requires in-depth study to balance the intentions of muzakki with shariah principles. This study is qualitative in nature, using descriptive data analysis. The primary sources related to the implementation of E-Zakat were obtained directly from interviews with the director and finance department of BAZNAS Surabaya, while the main data for analysis were taken from arguments based on the maq>asid shariah. The research findings show that the implementation of E-Zakat is based on the principles of transparency, email delivery, and religious promotion. The concept of transparency integrates the principles of maq>asid shariah, which consist of hifd al-maal, hifdz al-diin, and hifdz an-nafs. The preservation of wealth is achieved by protecting the identity of zakat givers, distributing funds productively, and reporting regularly; the preservation of religion is represented through spiritual messages; while the preservation of life is integrated by ensuring the allocation of zakat funds to priority recipients to strengthen humanity.